Decompositional Extraction and Retrieval of Conceptual Knowledge - Terletskyi, D.O.; Yershov, S.V. (Проблеми програмування, 2022)
An ability to extract hidden and implicit knowledge, their integration into a knowledge base, and then retrieval of required knowledge items are important features of knowledge processing for many modern knowledge-based systems. However, the complexity of these tasks depends on the size of knowledge sources, which were used for extraction, the size of a knowledge base, which is used for the integration of extracted knowledge, as well as the size of a search space, which is used for the retrieval of required knowledge items. Therefore, in this paper, we analyzed the internal semantic dependencies of homogeneous classes of objects and how they affect the decomposition of such classes. Since all subclasses of a homogeneous class of objects form a complete lattice, we applied the methods of formal concept analysis for the knowledge extraction and retrieval within the corresponding concept lattice. We found that such an approach does not consider internal semantic dependencies within a homogeneous class of objects, consequently, it can cause inference and retrieval of formal concepts, which are semantically inconsistent within a modeled domain. We adapted the algorithm for the decomposition of homogeneous classes of objects, within such knowledge representation model as object-oriented dynamic networks, to perform dynamic knowledge extraction and retrieval, adding additional filtration parameters. As the result, the algorithm extracts knowledge via constructing only semantically consistent subclasses of homogeneous classes of objects and then filters them according to the attribute and dependency queries, retrieving knowledge. In addition, we introduced the decomposition consistency coefficient, which allows estimation of how much the algorithm can reduce the search space for knowledge extraction and improves the performance. To demonstrate some possible application scenarios for the improved algorithm, we provided an appropriate example of knowledge extraction and retrieval via decomposition of a particular homogeneous class of objects. Можливості видобувати приховані та неявні знання, інтегрувати їх у базу знань, а потім здійснювати пошук необхідних елементів знань є важливими особливостями обробки знань для багатьох сучасних систем на основі знань. Однак складність цих задач залежить від розміру джерел знань, які використовувалися для видобування, обсягу бази знань, яка використовується для інтеграції видобутих знань, а також розміру простору пошуку, який використовується для пошуку необхідних елементів знань. Тому у даній статті ми проаналізували внутрішні семантичні залежності однорідних класів об’єктів і те, як вони впливають на декомпозицію таких класів. Оскільки всі підкласи однорідного класу об’єктів утворюють повну решітку, ми застосували методи аналізу формальних концептів для вилучення та пошуку знань у відповідній концептуальній ґратці. Ми виявили, що такий підхід не враховує внутрішні семантичні залежності в однорідному класі об’єктів, а отже, це може спричинити виведення і пошук формальних понять, які є семантично некоректними у межах галузі знань, що моделюється. Ми адаптували алгоритм декомпозиції однорідних класів об’єктів для такої моделі представлення знань, як об’єктно-орієнтовані динамічні мережі, додавши додаткові параметри фільтрації для динамічного видобування та пошуку знань. У результаті алгоритм видобуває знання шляхом побудови лише семантично коректних підкласів однорідних класів об’єктів, а потім фільтрує їх відповідно до запитів щодо атрибутів та залежностей, виконуючи пошук знань. Крім того, ми ввели коефіцієнт узгодженості декомпозиції, який дозволяє оцінити, наскільки алгоритм може зменшити простір пошуку для видобування знань і покращити продуктивність. Для демонстрації деяких можливих сценаріїв застосування вдосконаленого алгоритму ми навели відповідний приклад видобування та пошуку знань за допомогою декомпозиції конкретного однорідного класу об’єктів.